Pengaruh Kualitas Layanan, Kemudahan Penggunaan, Dan Kepercayaan Terhadap Keputusan Pembelian Dengan Word Of Mouth Sebagai Variabel Intervening Pada Pengguna Shopee (Studi Pada Mahasiswa Manajemen Universitas Muhammadiyah Metro Angkatan 2019) - Devita Febrianti; Jati Imantoro; Muhammad Dzaki Ramadan (Universitas Muhammadiyah Metro, 2025)
This is study aims to determine the direct effect between service quality, ease 0f use, and trust in purchasing decisions with word of mouth as an intervening variable. This research is a quantitative research by measuring the variables of service quality, ease of use and trust by using a closed questionnaire. The questionnaire scoring scale for each variable is 1-5 so that the range of scores obtained by respondents is between 20-100. Data collection was carried out by distributing questionnaires to a sample of 50 respondents. Data analysis in this study used path analysis with the help of the SPSS Version 25.0 application. The results of study show that there is a direct influence between service quality and word of mouth for shopee users. There is a direct effect of ease of use on word of mouth for shopee users. There is a direct effect of trust in word of mouth on shopee users. There is a direct effect of service quality on purchasing decisions for shopee users. There is a direct of ease of use purchasing decisions for shopee users. There is a direct influence of trust in purchasing decisions for shopee users. There is a direct influence of word of mouth on purchasing decisions for shopee users